#SaveBenjy: Sexuality, Queer Animals, and Ireland - Mc Loughlin, Eimear (Humanimalia, 2015)
This paper explores the #SaveBenjy Crowdfunder campaign to save a Charolais bull in the Republic of Ireland who expressed sexual interest only in weanling bulls and not the heifers he was expected to impregnate. The prominence and popularity of #SaveBenjy is anything but coincidental. In May 2015, the referendum on gay marriage sought to legalize same-sex marriage. Consequently, #SaveBenjy provides a timely lens through which to view Irish attitudes towards sexuality, while also raising important questions around nonhuman subjectivity and personhood. #SaveBenjy blurs the boundaries between nature and culture and thus, demands a new paradigm within which the nonhuman animal can be appreciated as being inherently and simultaneously natural and cultural.